Specialized Dental Care in the Brazilian Unified National Health System (SUS) - Samuel Trezena; Fabrício Emanuel Soares de Oliveira; Verônica Oliveira Dias; Petrônio José de Lima Martelli; Daniella Reis Barbosa Martelli; Hercílio Martelli Júnior (Association of Support to Oral Health Research (APESB), 2023)
Objective: To analyze specialized dental care through access, demand and the work processes provided by the CEO's, using secondary data from the cycles of the PMAQ-CEO. Material and Methods: Cross-sectional study using public domain data. Variables of interest were selected from the external evaluation instrument data matrices and were grouped in categories. The categories were geographic distribution, structural, human resources, work processes and access and coordination. Results: The total of 932 CEO's were evaluated in 2014 and 1,042 in 2016, most of them type II, present in the Northeast region. In both cycles, the highest average of dentists worked in the endodontic specialty (2.4 professionals per CEO) and the lowest in oral medicine (0.8 professionals per CEO). Of the two cycles, 91.5% of the CEO's had a manager, 79.5% performed action planning activities and 74.5% realized internal self-assessment processes. There was an increase in the mean number of days to be seen at the CEO in all analyzed specialties (p<0.001) and 85.2% of the CEO's managers reported that there is a reference for oral cancer confirmed cases. Conclusion: Between the PMAQ-CEO cycles the number of CEO has increased, but there are still a big pent-up demand and the presence of care gaps. However, an expansion and improvement of the CEO's actions was evidenced, mainly related to the work processes.